Perancangan Fasilitas Kerja Ergonomis Menggunakan Pendekatan Antropometri pada Stasiun Kerja Pemotongan - Fadel, Muhammad; Achiraeniwati, Eri (Bandung Conference Series: Industrial Engineering Science, 2023)
Abstract. Work facilities are important for a work environment that supports the smooth operation of operators. CV. Nur Rahmat Teknik is a company that produces heating elements. At the cutting work station, the operator's attitude is unnatural, such as squatting, bending the back, bowing the neck which is at risk of developing musculoskeletal disorders. The research objective of designing cutting work facilities is to reduce risk. The method used to identify risks is using the Nordic Body Map, risk determination is using the Workplace Ergonomic Risk Assessment method and designing work facilities using Anthropometry. The identification results of complaints and pain were found in the neck, upper back, lower back, shoulders, buttocks/thighs causing discomfort. The risks experienced by workers are at a medium level, meaning that further identification is needed and changes in work patterns are recommended. The proposed design is in the form of a work table with multifunction, namely a work table that can place all cutting tools, a storage area for scissors, grinders, knife blades. Simulation is carried out by Catia V5 simulation with low risk results, meaning that the work is accepted and can be continued. The results of the work risk analysis on cutting produce a medium risk value. The proposed work facility design is in the form of work tables and pipe storage locations. The proposed table size is 120 cm long, 100 cm wide, 100 cm high. Along with an additional table 80 cm long, 100 cm wide and 100 cm high. Along with additional shelves with a height of 45 cm. The simulation results using CATIA V5 software show that the design of work facilities resulting from a risk assessment results in a low risk, this score indicates that the work is safe and there is no work risk. Abstrak. Fasilitas kerja penting bagi lingkungan kerja yang menunjang kelancaran operator bekerja. CV. Nur Rahmat Teknik merupakan perusahaan yang memproduksi heating element. Pada stasiun kerja pemotongan sikap operator tidak alamiah seperti jongkok, punggung membungkuk, leher menunduk yang berisiko terjadinya musculoskeletal disorder. Tujuan penelitian untuk mengurangi risiko. Metode yang digunakan untuk mengidentifikasi risiko menggunakan Nordic Body Map, penentuan risiko dengan metode Workplace Ergonomic Risk Assessment dan perancangan fasilitas kerja menggunakan Antropometri. Hasil identifikasi keluhan dan rasa sakit didapatkan pada leher, punggung atas, punggung bawah, bahu, bokong/paha sehingga menimbulkan ketidaknyamanan. Risiko yang dialami pekerja pada level medium artinya perlu identifikasi lagi dan disarankan perubahan postur kerja. Rancangan yang diusulkan berupa meja dengan multifungsi yaitu meja kerja yang dapat menempatkan seluruh alat potong, tempat penyimpanan gunting, gerinda, mata pisau. Simulasi rancangan dilakukan dengan simulasi Catia V5 dengan hasil risiko pada level low artinya pekerjaan diterima dan dapat dilanjutkan. Hasil analisis risiko kerja pada pemotongan menghasilkan nilai risiko medium. Usulan perancangan fasilitas kerja berupa meja kerja dan letak penyimpanan pipa. Ukuran usulan meja adalah panjang meja 120 cm, lebar 100 cm, tinggi 100 cm. Beserta meja tambahan panjang 80 cm, lebar 100 cm, dan tinggi 100 cm. Beserta tambahan rak dengan tinggi 45 cm. Hasil simulasi menggunakan software CATIA V5 didapat perancangan fasilitas kerja hasil penilaian risiko menghasilkan risko rendah (low), skor tersebut mengindikasikan bahwa pekerjaan aman dan tidak ada risiko kerja yang ditimbulkan.